Factors associated with academic performance among students of the Faculty of Medicine, University of Jaffna - Insha, I.S.F.; Aakeela Shahana, M.Z.; Irhaam, M.F.M.; Kamshalini, S.; Waseefa, J.F.; Rajeev, G.; Surenthirakumaran, R. (University of Jaffna, 2024)
Background and objective: Education is crucial in the era of globalization and technological revolution. Students undergo various stages of education, with academic performance being measured through various methods. Factors affecting academic performance include socio-demographic, academic-related, and lifestyle related factors. This study aimed to assess the socio-demographic factors, academic-related factors, and lifestyle-related factors associated with academic performance among the students of Faculty of Medicine, University of Jaffna. Methods: A descriptive cross-sectional study was conducted with 429 students across selected batches from the Faculty of Medicine, University of Jaffna. Data were collected using a self-administered questionnaire and analysed using SPSS. Chi-square test was used to assess the association of selected factors with academic performance. Results: A majority in the sample were females (n=266, 62%). Most had got through the G.C.E Advanced Level (A/L) in their first attempt with passes in all three subjects (n=237, 55.2%). The proportion of female students who got through the First Examination for Medical Degrees in their first attempt was higher than the males (60.4%, p value=0.007). The proportion of students who got through in their first attempt was higher than the proportion who got through in the second and third attempts (71.8%, p value<0.001). A higher proportion of students who did their A/L in the English medium got through the examination compared to the students who did their A/L in their native language (56.1%, p value<0.001). All other factors that were assessed did not show any significant association with academic performance. Conclusion and recommendations: Except gender, attempt of entry and A/L medium, all other factors assessed showed no significant association with academic performance. Diverse teaching methods are recommended as different types of learners were identified. A mandatory attendance policy could be implemented as the students who were absent for fewer lectures showed higher academic performance. Substance abuse awareness as having a negative impact on academic performance has been observed and we recommend expanding the scope of research as many factors associated with academic performance are yet to be investigated.
Keywords: Academic performance; Medium of instruction; Teaching-learning activities; Medical education; Sri Lanka